Ameliorative potential of Anacyclus pyrethrum extract in generalized seizures in rat: Possible cholinergic mediated mechanism - Bezza, Kenza; Gabbas, Zineb El; Laadraoui, Jawad; Laaradia, Mehdi Ait; Oufquir, Sara; Chait, Abderrahman (Bangladesh Journal of Pharmacology, 2019)
The present study evaluates the anticonvulsant activity of the roots of Anacyclus pyrethrum using pilocarpine-induced experimental model of epilepsy in rat, and to determine its possible anticonvulsant mechanism. Ethanol extract (200 and 400 mg/kg) or alkylamides (25 and 50 mg/kg) was administered orally 45 min before the injection of pilocarpine-induced (400 mg/kg) seizures. The possible anticonvulsant mechanism was investigated by testing the effect of atropine (2 mL/kg) and scopolamine (1 mg/kg). The scoring of seizure severity, seizures time latency, duration of total seizures and percentage of mortality protection were recorded. Ethanol extract and alkylamides prolonged the time of onset seizure and decreased the duration of seizures compared to control group (p<0.001). The seizure protection was 100%. The co-administered of ethanol extract of A. pyrethrum and alkylamides with atropine completely abolished the pilocarpine-induced seizures. Video Clip of Methodology: Anticonvulsant effect: 6 min 7 sec: Click to watch